The beginning of the program of multiorgan postmortem donation and transplantation in the Republic of Sakha (Yakutia) - S. S. Meshcherin; O. V. Tatarinova; A. I. Vasiliev; A. G. Zolotareva; E. V. Tyryshkina; L. M. Alekseeva; A. A. Timofeev; B. V. Andreev; S. M. Khomyakov (Вестник трансплантологии и искусственных органов, 2018)
The article is devoted to the main aspects of organization of multiorgan donation from donors with brain death in the Republic of Sakha (Yakutia). Transplant services  to the population of this region have been in place since 2001, and until  2016 only kidney transplants or liver fragments from a living related donor have  been performed. The presence of an effective postmortem donation program will  allow to meet the high demand of this region for high-tech assistance by organ transplantation.